Isolation and characterization of SNPs within HSC70 gene in the freshwater prawn Macrobrachium amazonicum - Blanck, Danielly Veloso; Valenti, Wagner Cotroni [UNESP]; de Freitas, Patrícia Domingues; Galetti Junior, Pedro Manoel (Springer Nature, 2013)
We report the discovery of 13 synonymous single nucleotide polymorphisms (SNPs) within a fragment of HSC70 gene in Macrobrachium amazonicum. Polymorphisms were assessed using the reference sequence of the HSC70 gene in Macrobrachium rosenbergii to the primers design. The minor allele frequency ranged from 0.011 to 0.213. None of the SNPs deviated significantly from Hardy-Weinberg equilibrium. These SNPs will be useful to access the genetic variation of populations and to the study of their relations with characteristics of interest for aquaculture. Both cases, favoring the conservation of the natural stocks of Amazon river prawn. © 2013 Springer Science+Business Media Dordrecht.
Keywords: Amazon river prawn; Crustacean genetics; Heat shock protein; Single nucleotide polymorphisms